Contract enforcement, institutions and social capital: the Maghribi traders reappraised - Jeremy S. S. Edwards; Sheilagh Ogilvie (Center for Economic Studies and ifo Institute (CESifo), 2008)
Economists draw important lessons for modern development from the medieval Maghribi traders who, according to Greif, enforced contracts multilaterally through a closed, private-order coalition'. We show that this view is untenable. The Maghribis used formal legal mechanisms and entered business associations with non-Maghribis. Not a single empirical example adduced by Greif shows that any coalition' actually existed. The Maghribis cannot be used to argue that the social capital of exclusive networks will facilitate exchange in developing economies. Nor do they provide any support for the cultural theories of economic development and institutional change for which they have been mobilised.
Keywords: O17; 330; contract enforcement; reputation; legal system; social network; Vertrag; Normbefolgung; Prestige; Soziales Netzwerk; Außenhandelsgeschichte; Mittelalter; Mittelmeerraum